The ESCRT‐I components VPS28A and VPS28B are essential for auxin‐mediated plant development. (8th November 2020) - Liu, Jianyang; Wang, Yanning; Cheng, Youfa
SUMMARY: The highly conserved endosomal sorting complex required for transport (ESCRT) pathway plays critical roles in endosomal sorting of ubiquitinated plasma membrane proteins for degradation. However, the functions of many components of the ESCRT machinery in plants remain unsolved. Here we show that the ESCRT‐I subunits VPS28A and VPS28B are functionally redundant and required for embryonic development in Arabidopsis. We conducted a screen for genetic enhancers of pid, which is defective in auxin signaling and transport. We isolated a n o‐‐c otyledon in p id 104 ( ncp104 ) mutant, which failed to develop cotyledons in a pid background. We discovered that ncp104 was a unique recessive gain‐of‐function allele of vps28a . VPS28A and VPS28B were expressed during embryogenesis and the proteins were localized to the trans‐Golgi network/early endosome and post‐Golgi/endosomal compartments, consistent with their functions in endosomal sorting and embryogenesis. The single vps28a and vps28b loss‐of‐function mutants did not display obvious developmental defects, but their double mutants showed abnormal cell division patterns and were arrested at the globular embryo stage. The vps28a vps28b double mutants showed altered auxin responses, disrupted PIN1‐GFP expression patterns, and abnormal PIN1‐GFP accumulation in small aberrant vacuoles. The ncp104 mutation may cause the VPS28A protein to become unstable and/or toxic. Taken together, our findings demonstrate that the ESCRT‐I components VPS28A and VPS28B redundantly play essential roles in vacuole formation, endosomal sorting of plasma membrane proteins, and auxin‐mediated plant development. Significance Statement: We report here that the ESCRT‐I components VPS28A and VPS28B redundantly play essential roles in vacuole formation, endosomal sorting of plasma membrane proteins, and auxin‐mediated plant development. The recessive gain‐of‐function allele of vps28a/ncp104 can be used in future studies on post‐embryonic development; it may provide a unique tool and insights to explore the function of VPS28A and other ESCRT‐related proteins in both plants and other organisms.